Primary battery

The primary battery with iron oxyhydroxide and magnesium or aluminum electrodes, along with an aqueous electrolyte, addresses the issues of long-term storage and environmental impact by eliminating air intake ports and using non-rare materials, ensuring safe and efficient operation.

JP7602148B2Active Publication Date: 2024-12-18NIPPON TELEGRAPH & TELEPHONE CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2022563535
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-11-20
Publication Date
2024-12-18
Estimated Expiration
2040-11-20

AI Technical Summary

Technical Problem

Conventional batteries, particularly air batteries, suffer from electrolyte evaporation through air intake ports, making them unsuitable for long-term storage and relying on rare metals that contribute to resource depletion and environmental impact.

Method used

A primary battery design utilizing a positive electrode made of iron oxyhydroxide, a negative electrode made of magnesium or aluminum, and an aqueous electrolyte, eliminating the need for an air intake port and reducing environmental impact.

Benefits of technology

The battery can be stored for extended periods without electrolyte volatilization and has a lower environmental footprint due to the use of abundant materials, enhancing safety and disposal ease.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007602148000002
    Figure 0007602148000002
  • Figure 0007602148000003
    Figure 0007602148000003
  • Figure 0007602148000004
    Figure 0007602148000004
Patent Text Reader

Abstract

Provided is a primary battery comprising: a positive electrode 101 containing iron oxyhydroxide; a negative electrode 103 containing magnesium or aluminum; and an electrolyte 102 disposed between the positive electrode 101 and the negative electrode 103.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to primary batteries. [Background technology]

[0002] Conventionally, disposable primary batteries and rechargeable secondary batteries such as alkaline batteries, manganese batteries, high-performance coin-type lithium primary batteries, nickel-cadmium batteries, nickel-metal hydride batteries, and lithium-ion batteries have been widely used in small devices, sensors, mobile equipment, etc. In addition, with the recent development of the Internet of Things (IoT), development of scattered sensors that are installed throughout the natural world, such as in soil and forests, is also progressing.

[0003] Most of the batteries currently in common use are made up of rare metals such as lithium, nickel, manganese, and cobalt, and there is a problem of resource depletion.

[0004] Furthermore, air batteries with low environmental impact are being investigated (Patent Document 1). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] WO2018 / 003724 Summary of the Invention [Problem to be solved by the invention]

[0006] The battery principle of Patent Document 1 is an air battery, which uses oxygen in the air as a positive electrode active material, so an air inlet is essential for the battery. Therefore, air batteries have the disadvantage that the electrolyte evaporates from the air inlet, making them unsuitable for long-term storage. Therefore, there is a demand for a new battery with low environmental impact that can perform battery reactions in a closed system.

[0007] The present invention has been made in view of the above circumstances, and has an object to provide a primary battery that has a low environmental impact and can be stored for a long period of time. [Means for solving the problem]

[0008] A primary battery according to one embodiment of the present invention includes a positive electrode containing iron oxyhydroxide, a negative electrode containing magnesium or aluminum, and an electrolyte disposed between the positive electrode and the negative electrode. Effect of the Invention

[0009] According to the present invention, a primary battery that has a low environmental impact and can be stored for a long period of time can be provided. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a basic schematic diagram of a primary battery of this embodiment. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing the structure of a coin-type primary battery. [Figure 3A] FIG. 3A is a configuration diagram showing an example of a configuration of a bipolar type stack primary battery. [Figure 3B] FIG. 3B is a plan view showing a configuration example of a bipolar type stack primary battery. [Figure 4] 2 is a graph showing a discharge curve of the primary battery of Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, an embodiment of the present invention will be described with reference to the drawings.

[0012] [Primary battery configuration] 1 is a diagram showing the configuration of a primary battery according to an embodiment of the present invention. This primary battery includes a positive electrode 101 containing iron oxyhydroxide, a negative electrode 103 containing magnesium or aluminum, and an electrolyte 102 disposed between the positive electrode 101 and the negative electrode 103. As the electrolyte 102, it is preferable to use an aqueous electrolyte solution 102. In the embodiment described below, a case where the aqueous electrolyte solution 102 is used as the electrolyte 102 will be described as an example, but the present invention is not limited to this.

[0013] Specifically, the positive electrode 101 is configured using iron oxyhydroxide as an active material. The negative electrode 103 is configured using magnesium or aluminum as an active material. An aqueous electrolyte (electrolyte) 102 is disposed so as to be in contact with the positive electrode 101 and the negative electrode 103. Thus, the primary battery of this embodiment is characterized in that the positive electrode 101 contains an active material of iron oxyhydroxide, and the negative electrode 103 contains an active material of magnesium or aluminum.

[0014] The discharge reaction at the positive electrode 101 can be expressed as follows.

[0015] 2FeOOH+2H2O+2e - →2Fe(OH)2+2OH - (1) The hydroxide ion (OH - ) dissolves from the positive electrode 101 into the aqueous electrolyte solution 102 by electrochemical reduction, and migrates through the aqueous electrolyte solution 102 to the surface of the negative electrode 103.

[0016] The discharge reaction in the negative electrode 103 can be expressed as follows: As an example, the reaction when magnesium (Mg) is used for the negative electrode 103 is shown below.

[0017] Mg+2OH - →Mg(OH)2+2e - (2) The hydroxide ion (OH -Magnesium hydroxide (Mg(OH)2) is produced (precipitated) by the reaction between magnesium (Mg) and the negative electrode 103. When aluminum (Al) is used for the negative electrode 103, aluminum hydroxide (Al(OH)3) is precipitated in the same manner as with magnesium (Mg).

[0018] Discharge is possible through the reactions of formulas (1) and (2), and the overall reaction can be expressed as follows:

[0019] 2FeOOH+Mg+2H2O→2Fe(OH)2+Mg(OH)2...(3) In addition, the theoretical electromotive force is approximately 1.7 V (when α-FeOOH is used as the positive electrode active material and Mg is used as the negative electrode active material) and approximately 1.6 V (when α-FeOOH is used as the positive electrode active material and Al is used as the negative electrode active material).

[0020] The primary battery of the present embodiment uses iron oxyhydroxide as the positive electrode active material, magnesium or aluminum as the negative electrode active material, and an aqueous electrolyte solution as the electrolyte, and is therefore expected to be a battery made of inexpensive materials and with a low environmental impact.

[0021] The positive electrode 101 may contain a positive electrode active material and a conductive assistant as components. In addition, the positive electrode 101 preferably contains a binder for binding the above materials together.

[0022] The negative electrode 103 may contain a negative electrode active material and a conductive assistant as components. In addition, the negative electrode 103 preferably contains a binder for binding the above materials together.

[0023] Each of the above components will be described below.

[0024] (1) Positive electrode The positive electrode contains at least a positive electrode active material, and may contain additives such as a conductive assistant, a binder, etc. The positive electrode may be formed on a sheet-shaped current collector containing at least one selected from the group consisting of copper, iron, and carbon.

[0025] (1-1) Positive electrode active material The positive electrode active material of this embodiment contains at least iron oxyhydroxide (FeOOH). Iron oxyhydroxide exists in four different crystal phases, namely, α-phase, β-phase, γ-phase, and δ-phase, but the α-phase is preferred from the viewpoints of cost and productivity.

[0026] The particle size of the positive electrode active material is preferably 0.3 μm to 10 μm, and more preferably 0.5 μm to 5 μm.

[0027] This is because, while the smaller the particle size, the more reactive sites there are and the better the output performance, repeated charge-discharge cycles impair the electrical contact with the positive electrode active material, conductive additive, and current collector, resulting in a decrease in cycle performance.

[0028] Iron oxyhydroxide can be produced by existing methods, such as oxidizing iron hydroxide (Fe(OH)2) in a pH-controlled aqueous solution, heating an aqueous solution of iron chloride (FeCl3), or adding hydrogen peroxide (H2O2) to an iron hydroxide (Fe(OH)2) dispersion. It is also possible to use commercially available iron oxyhydroxide.

[0029] (1-2) Conductive additive In this embodiment, the positive electrode may contain a conductive assistant. For example, carbon can be used as the conductive assistant. Specifically, carbon blacks such as Ketjen black and acetylene black, activated carbons, graphites, carbon fibers, etc. can be mentioned. In order to secure sufficient reaction sites in the positive electrode, carbon with small particles is suitable. Specifically, carbon with a particle diameter of 1 μm or less is preferable. These carbons can be obtained, for example, as commercial products or by known synthesis.

[0030] The positive electrode active material may be directly coated with carbon. Coating methods include physical methods such as vapor deposition, sputtering, and planetary ball milling, chemical methods such as coating with an organic material and then heat treating the material, and known coating methods.

[0031] (1-3) Binder The positive electrode may contain a binder. The binder is not particularly limited, but examples thereof include polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), styrene butadiene rubber, ethylene propylene diene rubber, and natural rubber. From the viewpoint of environmental load and waste disposal, styrene butadiene rubber, ethylene propylene diene rubber, and natural rubber that do not use fluorine are more preferable.

[0032] These binders can be used as powders or as dispersions.

[0033] The contents of the positive electrode active material, conductive assistant, and binder in the positive electrode of this embodiment are, based on the weight of the entire positive electrode, such that the positive electrode active material is greater than 0% by weight and not more than 99%, and preferably 70 to 95% by weight, the conductive assistant is 0 to 90% by weight, and preferably 1 to 30% by weight, and the binder is 0 to 50% by weight, and preferably 1 to 30% by weight.

[0034] (1-4) Preparation of positive electrode The positive electrode can be prepared as follows: The positive electrode active materials, iron oxyhydroxide powder, carbon powder, and, if necessary, a dispersion liquid such as styrene-butadiene rubber are mixed, and the mixture is applied to a current collector and dried to form a positive electrode.

[0035] The current collector is not particularly limited, but for example, a sheet-like or mesh-like current collector using at least one (one element) selected from the group consisting of copper, iron, titanium, nickel, and carbon can be used.

[0036] In order to assemble a battery into a bipolar stack structure described later, the current collector is preferably in a sheet form. From the viewpoint of environmental load and disposal, a sheet-shaped current collector containing at least one selected from the group consisting of copper, iron, and carbon is more preferable. In this way, the positive electrode is preferably applied to a sheet-shaped current collector containing at least one selected from the group consisting of copper, iron, and carbon.

[0037] In order to increase the strength of the electrode, the electrode after drying can be subjected to cold pressing or hot pressing, thereby making it possible to fabricate a more stable positive electrode.

[0038] As described above, by preparing a positive electrode containing iron oxyhydroxide as a positive electrode active material, a positive electrode that is highly active in charge and discharge reactions can be obtained. Furthermore, by preparing a positive electrode for a primary battery having the above-mentioned configuration, it is possible to fully utilize the potential of iron oxyhydroxide as a positive electrode active material.

[0039] (2) Negative electrode The negative electrode contains at least a negative electrode active material, and may contain additives such as a conductive assistant, a binder, etc. The negative electrode may be formed on a sheet-shaped current collector containing at least one selected from the group consisting of copper, iron, and carbon.

[0040] (2-1) Negative electrode active material The negative electrode active material of this embodiment contains at least magnesium (Mg) or aluminum (Al).

[0041] The negative electrode active material may contain magnesium (Mg) or aluminum (Al) as a main component, and may also be an alloy containing at least one component selected from the group consisting of zinc (Zn), calcium (Ca), lithium (Li), manganese (Mn), iron (Fe), tin (Sn), and carbon (C).

[0042] The negative electrode active material can be produced by forming a magnesium (Mg) foil or an aluminum (Al) foil into a predetermined shape.

[0043] Magnesium (Mg) or aluminum (Al) may be used in powder form. However, when used in powder form, the number of reactive sites increases, improving output performance, but the oxidation of magnesium (Mg) or aluminum (Al) and the corrosion caused by the electrolyte accelerate. For this reason, it is preferable to use magnesium (Mg) or aluminum (Al) in foil or bulk form.

[0044] (2-2) Conductive additive When the negative electrode active material is used in the form of a powder, the negative electrode may contain a conductive assistant. For example, carbon can be used as the conductive assistant. Specifically, carbon blacks such as ketjen black and acetylene black, activated carbons, graphites, carbon fibers, etc. can be mentioned. In order to ensure sufficient reaction sites in the negative electrode, carbon with small particles is suitable. Specifically, a particle diameter of 1 μm or less is desirable. These carbons can be obtained, for example, as commercial products or by known synthesis.

[0045] The negative electrode active material may be directly coated with carbon. Coating methods include physical methods such as vapor deposition, sputtering, and planetary ball milling, chemical methods such as coating with an organic material and then heat treating the material, and known coating methods.

[0046] (2-3) Binder When the negative electrode active material is used in the form of powder, the negative electrode may contain a binder. The binder is not particularly limited, but examples thereof include polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), styrene butadiene rubber, ethylene propylene diene rubber, and natural rubber. From the viewpoint of environmental load and waste disposal, styrene butadiene rubber, ethylene propylene diene rubber, and natural rubber that do not use fluorine are more preferable. These binders can be used as powder or dispersion.

[0047] When the negative electrode active material is used in the form of powder, the contents of the negative electrode active material, conductive assistant, and binder are, based on the weight of the entire negative electrode, such that the negative electrode active material is greater than 0% by weight and not more than 99%, and preferably 70 to 95% by weight, the conductive assistant is 0 to 90% by weight, and preferably 1 to 30% by weight, and the binder is 0 to 50% by weight, and preferably 1 to 30% by weight.

[0048] (2-4) Preparation of negative electrode The negative electrode can be prepared as follows: Magnesium (Mg) or aluminum (Al) is processed into a predetermined shape, and this negative electrode active material is attached to a current collector by welding or the like to form the negative electrode.

[0049] The current collector is not particularly limited, but for example, a sheet-like or mesh-like current collector using at least one (one element) selected from the group consisting of copper, iron, titanium, nickel, and carbon can be used.

[0050] In order to assemble a battery into a bipolar stack structure described later, the current collector is preferably in a sheet form. From the viewpoint of environmental load and disposal, a sheet-shaped current collector containing at least one selected from the group consisting of copper, iron, and carbon is more preferable. Thus, the negative electrode is preferably formed on a sheet-shaped current collector containing at least one selected from the group consisting of copper, iron, and carbon.

[0051] When the negative electrode active material is used in powder form, it can be prepared as follows: The negative electrode active material magnesium (Mg) powder or aluminum (Al) powder, carbon powder, and, if necessary, a dispersion liquid such as styrene-butadiene rubber are mixed, and the mixture is applied to a current collector and dried to form a negative electrode.

[0052] In order to increase the strength of the electrode, the electrode after drying can be subjected to cold pressing or hot pressing, thereby making it possible to produce a negative electrode with superior stability.

[0053] As described above, by preparing an anode containing magnesium (Mg) or aluminum (Al) as an anode active material, a highly active anode can be obtained. Furthermore, by preparing an anode for a primary battery having the above-mentioned configuration, it is possible to fully utilize the potential of magnesium (Mg) or aluminum (Al) as an anode active material.

[0054] (3) Aqueous electrolyte (electrolyte) The primary battery of this embodiment contains an aqueous electrolyte. This aqueous electrolyte converts hydroxide ions (OH - ) is an aqueous solution containing an electrolyte capable of moving. The aqueous electrolyte uses water as a main solvent and may contain a solvent other than water. For the aqueous electrolyte, for example, an aqueous solution in which at least one electrolyte selected from the group consisting of acetates, carbonates, phosphates, pyrophosphates, metaphosphates, citrates, borates, ammonium salts, formates, hydrogen carbonates, hydroxides, and chlorides is dissolved in water can be used.

[0055] In this embodiment, an aqueous electrolyte solution is used as the electrolyte, but a solid electrolyte such as a gel or solid may be used. That is, the electrolyte may be in any form such as a liquid, cream, gel, or solid. The electrolyte may be aqueous or non-aqueous.

[0056] When an acidic or alkaline aqueous solution is used as the aqueous electrolyte, the pH of the electrolyte is preferably 5.8 or more and 8.6 or less. Generally, the stronger the alkalinity of the electrolyte, the better the performance. However, the Water Pollution Control Act, which is a national law, stipulates that the allowable limit of the pH (hydrogen ion concentration) of wastewater discharged into public waters other than sea areas is 5.8 or more and 8.6 or less. For this reason, from the viewpoint of environmental load and waste disposal, the pH (hydrogen ion concentration) of the aqueous electrolyte is preferably 5.8 or more and 8.6 or less, even if it sacrifices performance.

[0057] (4) Other factors In addition to the above components, the primary battery of this embodiment can include structural members such as a separator and a battery case, and other elements required for a primary battery. These can be conventionally known materials, but from the viewpoint of environmental load and waste disposal, it is preferable that they do not contain harmful substances, rare metals, rare earths, etc. Furthermore, it is more preferable that these other elements are biologically derived and biodegradable materials.

[0058] (5) Manufacturing method of primary batteries As described above, the primary battery of this embodiment includes at least a positive electrode, a negative electrode, and an aqueous electrolyte, and the aqueous electrolyte is disposed between the positive electrode and the negative electrode so as to be in contact with the positive electrode and the negative electrode, as illustrated in Fig. 1. A primary battery having such a configuration can be prepared in the same manner as a conventional primary battery.

[0059] For example, a primary battery can be prepared by assembling the various components according to conventional technology, including a positive electrode active material containing the above-mentioned iron oxyhydroxide, a positive electrode containing a conductive additive and a binder, a negative electrode containing magnesium (Mg) or aluminum (Al), and an aqueous electrolyte solution disposed in contact with the positive electrode and the negative electrode.

[0060] (5-1) Manufacturing method of coin-type primary battery As an embodiment of the method for producing a primary battery, for example, a coin-type primary battery can be produced.

[0061] 2 is a schematic cross-sectional view showing the structure of a coin-type primary battery. Specifically, a separator (not shown) is placed on the positive electrode case 201 in which the positive electrode 101 is placed, and an electrolyte 102 is poured into the placed separator. Next, the negative electrode 103 is placed on the electrolyte 102, and the negative electrode case 202 is placed over the positive electrode case 201. Next, the peripheries of the positive electrode case 201 and the negative electrode case 202 are crimped with a coin cell crimping machine, whereby a coin-type primary battery including a propylene gasket 203 can be produced.

[0062] The coin-type primary battery shown in the figure uses iron oxyhydroxide powder as the positive electrode active material. Therefore, unlike an air battery that uses oxygen in the air as the positive electrode active material, there is no need to provide an air intake port in the positive electrode case 201 of this embodiment. That is, in this embodiment, a sealed battery can be produced. Therefore, the primary battery of this embodiment can be stored for a long period of time without the electrolyte volatilizing from the air intake port.

[0063] (5-2) Manufacturing method of bipolar stacked primary battery As an embodiment of the method for manufacturing a primary battery, for example, a primary battery having a bipolar type stack structure can be manufactured.

[0064] Fig. 3A is a configuration diagram showing a configuration example of a bipolar type stack primary battery, and Fig. 3B is a plan view showing a configuration example of a bipolar type stack primary battery.

[0065] In the primary battery of this embodiment, when the pH of the electrolyte used is 5.8 or more and 8.6 or less, output performance cannot be expected. For this reason, it is preferable to increase the output by forming a primary battery with a stack structure.

[0066] Specifically, first, the positive electrode 101 and the negative electrode 103 are bonded to both sides of a current collector 322 such as a copper foil, respectively, to form the positive electrode 101 and the negative electrode 103 on one current collector 322. In this way, a bipolar electrode 320 is produced in which the positive electrode 101 and the negative electrode 103 are each formed on one side of the current collector 322.

[0067] Moreover, each of the outermost current collectors 303A and 303B may have an electrode formed on only one side, and preferably has a tab 313A or 313B for taking out electricity. The outermost current collector 303A shown in the figure has a positive electrode 101 formed on only one side, and a tab 313A formed thereon. The outermost current collector 303B has a negative electrode 103 formed on only one side, and a tab 313B formed thereon.

[0068] Tabs 313A, 313B may be formed by processing current collectors 303A, 303B into a shape having protrusions, or separate metal tabs may be joined to current collectors 303A, 303B by ultrasonic welding, spot welding, or the like.

[0069] Current collector 322 on which positive electrode 101 and negative electrode 103 are formed is stacked so that positive electrode 101 and negative electrode 103 face each other, and separator 301 is inserted so as to be in contact with positive electrode 101 and negative electrode 103. Similarly, current collectors 303A and 303B for the outermost layer on which positive electrode 101 or negative electrode 103 are formed are stacked so that positive electrode 101 and negative electrode 103 face each other, and separator 301 is inserted so as to be in contact with positive electrode 101 and negative electrode 103.

[0070] After the current collectors 303A, 303B, 322 and the separator 301 are laminated, the peripheral portions of the copper foils of the current collectors are sealed by heat pressing using a heat fusion sheet 302. However, one side (part) of the peripheral portion needs to be left open and not heat pressed in order to inject an aqueous electrolyte solution, which will be described later.

[0071] The fabricated stack is sandwiched between aluminum laminate films 304 or the like, and an aqueous electrolyte is injected into each cell (each chamber). Then, the unsealed side of the stack and the peripheral portion of the aluminum laminate film are vacuum sealed to fabricate a bipolar type stack structure primary battery.

[0072] Such a primary battery is a sealed battery that does not require an air inlet, unlike an air battery that uses oxygen in the air as a positive electrode active material. Therefore, the primary battery of this embodiment can be stored for a long period of time without the electrolyte volatilizing through the air inlet.

[0073] [Example] Examples of the primary battery according to this embodiment will be described in detail below. In each example, a primary battery using magnesium (Mg) for the negative electrode and a primary battery using aluminum (Al) for the negative electrode were fabricated. Note that the present invention is not limited to the examples shown below, and can be modified appropriately within the scope of the present invention.

[0074] <Example 1> In Example 1, the above-mentioned coin-type primary battery (FIG. 2) was fabricated by the following procedure. Magnesium (Mg) foil and aluminum (Al) foil were used as the negative electrode active materials. The aqueous electrolyte contained 1.0×10 alkaline electrolyte (pH about 9). -4 A mol / L aqueous solution of potassium hydroxide (KOH) was used.

[0075] (Preparation of Positive Electrode) Iron oxyhydroxide powder (particle size 1 μm, Kojundo Chemical Laboratory), Ketjen black powder (EC600JD, Lion Specialty Chemicals), and polytetrafluoroethylene (PTFE) powder were thoroughly ground and mixed in a weight ratio of 80:10:10 using a grinding machine, and roll-formed to prepare a sheet electrode (thickness: 0.5 mm). This sheet electrode was cut into a circle with a diameter of 16 mm and pressed onto a copper mesh to obtain a positive electrode.

[0076] (Preparation of negative electrode) Magnesium (Mg) foil (thickness 150 μm, Nilaco Corporation) and aluminum (Al) foil (thickness 150 μm, Nilaco Corporation) were each cut into a circle with a diameter of 16 mm to obtain a negative electrode.

[0077] (Preparation of Primary Batteries) Using a coin battery case (Hosensha), a coin-type primary battery as shown in FIG. 2 was fabricated.

[0078] A cellulose separator (Nippon Kodo Shi Kogyo Co., Ltd.) cut to a diameter of 18 mm was placed on the positive electrode case 201 in which the positive electrode 101 prepared by the above method was installed, and 1.0×10 -4 A mol / L aqueous potassium hydroxide solution (KOH) is poured as the aqueous electrolyte 102. The negative electrode 103 is placed on the aqueous electrolyte 102, the negative electrode case 202 is placed over the positive electrode case 201, and the periphery of the positive electrode case 201 and the negative electrode case 202 are crimped with a coin cell crimping machine, thereby obtaining a coin-type primary battery including a propylene gasket 203.

[0079] (Battery performance) The battery performance of the primary battery prepared by the above procedure was measured. The battery cycle test was performed using a charge / discharge measurement system (manufactured by Bio Logic) at a current density of 1 mA / cm per effective area of ​​the positive electrode. 2 A current was passed through the battery, and the discharge voltage was measured until the battery voltage dropped from the open circuit voltage to 0.60 V. The battery discharge test was carried out under normal living conditions. The discharge capacity was expressed as the value per unit weight of the positive electrode active material (iron oxyhydroxide) (mAh / g).

[0080] Figure 4 shows the discharge curve when magnesium (Mg) is used for the negative electrode. It can be seen from Figure 4 that when iron oxyhydroxide is used for the positive electrode active material, the average discharge voltage is 1.08 V and the discharge capacity is 254 mAh / g. Here, the average discharge voltage is defined as the discharge voltage at half the total discharge capacity (here, 127 mAh / g).

[0081] The discharge voltage and discharge capacity of the primary batteries using magnesium (Mg) and aluminum (Al) for the negative electrode are shown in Table 1. As described above, it was found that each primary battery of Example 1 had excellent battery performance.

[0082] [Table 1]

[0083] <Example 2> In Example 2, the above-mentioned coin-type primary battery was fabricated by the following procedure. The positive electrode was prepared by coating a copper sheet-shaped current collector, and the negative electrode was prepared by welding to the copper sheet-shaped current collector. The aqueous electrolyte was an alkaline electrolyte (pH about 9) with 1.0×10 -4 The battery was fabricated and evaluated in the same manner as in Example 1.

[0084] (Preparation of Positive Electrode) Iron oxyhydroxide powder (particle size 1 μm, Kojundo Chemical Laboratory), Ketjen black powder (EC600JD, Lion Specialty Chemicals), and styrene butadiene rubber (AA Portable Power) were thoroughly mixed in a weight ratio of 80:10:10 using a kneader (Thinky Corporation) to prepare a slurry. This slurry was applied to copper foil (Nilaco Corporation) and dried in a vacuum dryer at 100°C for 12 hours. It was then pressed at 120°C, and the sheet-like electrode was cut into a circle with a diameter of 16 mm to obtain a positive electrode.

[0085] (Preparation of negative electrode) Magnesium (Mg) foil (thickness 150 μm, Nilaco Corporation) and aluminum (Al) foil (thickness 150 μm, Nilaco Corporation) were each cut into circles with a diameter of 16 mm, and each was bonded to copper foil (Nilaco Corporation) using an ultrasonic welding machine.

[0086] (Battery performance) The discharge capacity and discharge voltage of the primary battery of Example 2 are shown in Table 1. As shown in Table 1, the discharge capacity of Example 2 in the battery using magnesium (Mg) for the negative electrode was 270 mAh / g, which was a larger value than that of Example 1. The discharge capacity of Example 2 in the battery using aluminum (Al) for the negative electrode was also larger than that of Example 1.

[0087] Moreover, as shown in Table 1, the discharge voltage of Example 2 is higher than that of Example 1. That is, in Example 2, a reduction in overvoltage was observed compared to Example 1, and an improvement in the energy efficiency of discharge was achieved.

[0088] These improvements in characteristics are believed to be due to the fact that the positive and negative electrodes are bonded to copper sheet collectors, respectively, which reduces the internal resistance of the battery and facilitates smooth battery reactions.

[0089] <Example 3> In Example 3, the above-mentioned coin-type primary battery was fabricated by the following procedure. An aqueous ammonium chloride solution (NH4Cl) with a pH (hydrogen ion concentration) of 5.8 was used as the aqueous electrolyte. pH 5.8 is the allowable limit for wastewater discharged into public waters other than sea areas, as stipulated by the Water Pollution Prevention Law.

[0090] The preparation of the positive and negative electrodes, the production of the battery, and the evaluation method were the same as in Example 2, except for the aqueous electrolyte solution.

[0091] (Battery performance) The discharge capacity and discharge voltage of the primary battery of Example 3 are shown in Table 1. As shown in Table 1, the discharge capacity of Example 3 in the battery using magnesium (Mg) for the negative electrode was 251 mAh / g, which was equivalent to that of Example 1. The discharge capacity of Example 3 in the battery using aluminum (Al) for the negative electrode was also equivalent to that of Example 1.

[0092] Furthermore, as shown in Table 1, the discharge voltage was also equivalent to that of Example 1, and sufficient discharge energy efficiency was achieved even when an aqueous electrolyte solution with low environmental impact and high safety was used.

[0093] This is believed to be because the reaction efficiency of the primary battery of this embodiment is high, and the battery reaction proceeds smoothly even when a nearly neutral aqueous electrolyte is used.

[0094] <Example 4> In Example 4, the above-mentioned bipolar type primary battery having a three-stack structure was fabricated in the following manner.

[0095] 3A is an exploded view of a bipolar type three-stack primary battery. As in Example 3, an aqueous ammonium chloride solution (NH4Cl) with a pH (hydrogen ion concentration) of 5.8 was used as the aqueous electrolyte.

[0096] The battery was evaluated in the same manner as in Example 3. However, the charge / discharge test was continued until the discharge voltage decreased to 1.00V.

[0097] (Preparation of Positive and Negative Electrodes) As the negative electrode 103, magnesium (Mg) foil (thickness 150 μm, Nilaco Corporation) and aluminum (Al) foil (thickness 150 μm, Nilaco Corporation) were each cut into a size of 2 cm×2 cm, and these were joined to copper foil (Nilaco Corporation) using an ultrasonic welding machine.

[0098] Next, iron oxyhydroxide powder (particle size 1 μm, Kojundo Chemical Laboratory), Ketjen Black powder (EC600JD, Lion Specialty Chemicals), and styrene butadiene rubber (AA Portable Power) were mixed thoroughly using a kneader (Thinky Corporation) to a weight ratio of 80:10:10 to prepare a slurry for the positive electrode 101. This slurry was applied to the back side of the copper foil to which the negative electrode had been bonded, in an area of ​​2 cm x 2 cm, and dried in a vacuum dryer at 100°C for 12 hours. It was then pressed at 120°C to obtain a bipolar electrode 320 in which the positive electrode 101 and the negative electrode 103 were bonded on one side each.

[0099] However, the outermost positive electrode 101 and the outermost negative electrode 103 were bonded to only one side of the copper foil (current collectors 303A and 303B) described above. The preparation method was the same as above. The outermost copper foil (current collectors 303A and 303B) was cut out in a shape having tabs 313A and 313B.

[0100] (Preparation of Primary Batteries) Using the aluminum laminate film 304, a bipolar type primary battery having a three-stack structure shown in FIG. 3 was fabricated.

[0101] Two bipolar electrodes 320 prepared by the above method are stacked so that the positive electrode 101 and the negative electrode 103 face each other, and a separator 301 cut to 2.2 cm x 2.2 cm and a frame-shaped heat-sealing sheet 302 with a center cut out are inserted between the bipolar electrodes 320. After stacking, the three peripheral sides of each current collector 322 are sealed by heat pressing at 180°C.

[0102] The outermost layer is also formed in the same manner as above, with the negative electrode 103, positive electrode 101, separator 301, and heat-sealing sheet 302 stacked so that the positive electrode 101 and negative electrode 103 face each other, and the same three sides as those sealed above are sealed by heat pressing.

[0103] The stack thus produced is sandwiched between an aluminum laminate film 304 and a heat-sealing sheet 302, and the same three sides as the sealed sides described above are heat-pressed to make the aluminum laminate film into a bag shape.

[0104] Then, an aqueous ammonium chloride solution (NH4Cl) with a pH of 5.8 was injected into each cell (chamber) of the stack structure to thoroughly immerse the separator 301, and then the unsealed side of the aluminum laminate film 304 was vacuum sealed. Finally, the unsealed side of the stack was sealed from above the aluminum laminate film 304 to obtain a bipolar type stack primary battery.

[0105] Although three stacks are used in the fourth embodiment, a bipolar type stack primary battery having three or more stacks can also be fabricated, and in that case, the number of bipolar electrodes 320 to be stacked may be increased.

[0106] (Battery performance) The discharge capacity and discharge voltage of the primary battery of this example are shown in Table 1. As shown in Table 1, the discharge capacity of Example 4 in the battery using magnesium (Mg) for the negative electrode was 272 mAh / g, which was equivalent to that of Example 2. In the battery using aluminum (Al) for the negative electrode, the discharge capacity of Example 3 was also equivalent to that of Example 2.

[0107] In addition, as shown in Table 1, the discharge voltage is about three times that of Example 1, and by using a bipolar type stack-structure primary battery, it is possible to achieve a voltage equivalent to that of a conventional lithium-ion battery.

[0108] From the above results, the primary battery of this embodiment uses iron oxyhydroxide as the positive electrode active material and magnesium or aluminum as the negative electrode active material, thereby achieving low environmental impact and simplified disposal treatment.

[0109] Moreover, the primary battery of the present embodiment is a sealed battery that does not require an air intake port, unlike an air battery, and therefore can be stored for a long period of time without the electrolyte volatilizing through the air intake port.

[0110] It is preferable to use an aqueous electrolyte as the electrolyte. If an organic electrolyte is used, it may cause a fire or explosion because it is flammable, and there is a concern that leakage may have a negative effect on the human body and the environment. In contrast, in this embodiment, an aqueous electrolyte is used, making it possible to produce a safe and inexpensive battery.

[0111] The pH of the aqueous electrolyte is preferably 5.8 to 8.6, which makes it possible to produce an environmentally friendly battery that can be easily disposed of.

[0112] Therefore, the primary battery of this embodiment can be effectively used as a new driving source for various electronic devices such as small devices, sensors, and mobile devices.

[0113] The present invention is not limited to the above-described embodiment, and various modifications and combinations are possible within the technical concept of the present invention. [Explanation of symbols]

[0114] 101: Positive electrode 102:Aqueous electrolyte (electrolyte) 103: Negative electrode 201: Positive electrode case 202: Negative electrode case 203: Propylene gasket 301: Separator 302: Heat-sealing sheet 303A, 303B: Outermost current collector 304: Aluminum laminate film 320: Bipolar electrode 322: Current collector

Claims

1. A positive electrode including iron oxyhydroxide as a positive electrode active material; a negative electrode containing magnesium or aluminum; and an electrolyte disposed between the positive electrode and the negative electrode. Primary battery.

2. The electrolyte is an aqueous electrolyte solution, and the pH of the aqueous electrolyte solution is 5.8 or more and 8.6 or less.

10. The primary battery of claim 1.

3. The positive electrode and the negative electrode are formed on a sheet-shaped current collector containing at least one selected from the group consisting of copper, iron, and carbon. The primary battery according to claim 1 or 2.

4. A positive electrode containing iron oxyhydroxide; a negative electrode containing magnesium or aluminum; an electrolyte disposed between the positive electrode and the negative electrode; It has a bipolar stack structure Primary battery.

Citation Information

Patent Citations

  • Iron composite oxide battery

    JP2001283850A

  • Battery and method for producing positive electrode for same

    WO2018003724A1